The Toronto School of Communication Theory - Rita Watson, Menahem Blondheim (University of Toronto Press, 2008)
The â€œToronto Schoolâ€ insists that the technologies of the media of communication are far more influential than their content. Harold Adams Innis and Marshall McLuhan are not alone in making this claim, and not the earliest, but they have done so more provocatively and more persistently than others. Whatâ€™s more they argue that media technologies have a dominant influence not just on individuals but on social structure and culture, and not just in modern times but from the beginning. Their writings have attracted much interest â€“ and fierce debate â€“ but only little systematic research. If they are right, communications media deserve a central place in the history of civilizations, and communication research ought to rise to the challenge. But it hasnâ€™t. The bigness of these claims â€“ and the pride of place which they offer to the media â€“ contrasts sharply with the conclusion of â€œlimited effectsâ€ echoed repeatedly in studies of mass persuasion. These studies of media â€œcampaignsâ€ can be traced to the theory of mass society, suggesting that the atomized individuals of the early 20th century would be vulnerable â€“ as if by remote control â€“ to the ostensibly powerful appeals of broadcasters. However, the empirical research that set out to test this assumption â€“ at Columbia (Klapper, 1960) and at Yale (Hovland, 1959) â€“ found that it is far from easy to change opinions, attitudes and actions, and, moreover, that modern individuals are less isolated or alienated than was assumed. The claims of mainstream communications research became much more modest as a result.